The Norwegian journalism education landscape - Bjørnsen, Gunn; Hovden, Jan Fredrik; Ottosen, Rune (Žurnalistikos tyrimai, 2009)
Journalism is one of the most popular study programmes in Norway. There are several pathways into the Norwegian news industry for young people seeking a career in journalism, but it is increasingly common for aspiring journalists to start off with a journalism education. In this article the landscapeof Norwegian journalism education is presented, including a closer look at the content of the studies, the connection to the industry and the students of journalism themselves. The description of the students is based on a dataset from a series of questionnaires administered between 2000 and 2004 to three complete cohorts of Norwegian journalism students at Oslo University College and Volda University College, the largest and oldest J-schools in Norway. Norwegian journalism education can be described as working quite well as measured by both the students’ success in the job market and their expressed satisfaction with their studies. The fact that the application rate for several years has been among the very highest compared with other university programmes also validates this point.Keywords: Norway, journalism education, relation between industry and j-schools.p>